2005
DOI: 10.1074/jbc.m505737200
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Ligand-dependent and -independent Mechanisms for Mitogen-activated Protein Kinase Activation by the Murine Ron Receptor Tyrosine Kinase

Abstract: Receptor tyrosine kinases (RTKs) activate downstream signaling through cognate growth factor receptor-induced dimerization and autophosphorylation. Overexpression of RTKs can lead to constitutive activation due to increased dimerization in the absence of ligand, and downstream signals are presumed to be the same as the ligand-induced signals. We have shown that the murine Ron (mRon) receptor tyrosine kinase exhibits constitutive activation of the MAP kinase pathway that is independent of the two docking site t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…These results strongly suggest that the mechanisms of RON activation by RON overexpression and by MSP stimulation are different in these RON-expressing MDCK cells. Noticeably, phosphorylation of ERK/ MAPK but not Akt was also recently reported for the mouse Stk [14].…”
Section: Ron Activation Leads To Erk/mapk But Not Akt Phosphorylationmentioning
confidence: 97%
“…These results strongly suggest that the mechanisms of RON activation by RON overexpression and by MSP stimulation are different in these RON-expressing MDCK cells. Noticeably, phosphorylation of ERK/ MAPK but not Akt was also recently reported for the mouse Stk [14].…”
Section: Ron Activation Leads To Erk/mapk But Not Akt Phosphorylationmentioning
confidence: 97%
“…We have recently shown that c-Src associates with mRON in a ligand-independent manner through three tyrosines in the kinase domain and that Src activity is required for the ligand-independent activation of MAP kinase by mRON (28). When the activation of AP1 by the mRON and hRON receptors was compared in SYF cells lacking all Src family kinases, there was no significant difference in the levels of constitutive signaling between hRON and mRON, and both receptors induced AP1 transcriptional activity in response to ligand stimulation (Fig.…”
Section: A Deletion In the Juxtamembrane Domain Of Hron Confers Liganmentioning
confidence: 99%
“…RON mutations were introduced using a QuikChange Mutagenesis kit (Stratagene) and then were subcloned into murine stem cell virus-derived retroviral transfer vector MSCV2.1 as previously described (25,26). Receptor expression was confirmed by immunoblotting (22) using a rabbit anti-RON polyclonal Ab (Santa Cruz Biotechnology) and mouse anti-GAPDH (Fitzgerald) as a loading control.…”
Section: Cells and Cell Linesmentioning
confidence: 99%
“…Therefore, to gain further insight into mechanisms by which RON repress HIV-1 provirus transcription we used site-directed mutagenesis to generate several mutations in the RON cytoplasmic domain (25,26). In particular, we mutated Y1353 and Y1360, which serve as a multifunctional docking site for several signaling molecules including Gab-1, Grb2, PI3K, phospholipase C, and Src homology protein-2 (32).…”
Section: Signals Emanating From Ron Inhibit Hiv Transcriptionmentioning
confidence: 99%